2001
DOI: 10.1248/cpb.49.830
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships of N-(3,5-Dimethoxy-4-n-octyloxycinnamoyl)-N'-(3,4-dimethylphenyl)piperazine and Analogues as Inhibitors of Acyl-CoA: Cholesterol O-Acyltransferase.

Abstract: Since the pioneering results of the Framingham study disclosed in 1971, 1) hypercholesterolemia has been recognized as a major risk factor for the development of coronary heart disease (CHD).2,3) Agents controlling total plasma cholesterol levels are expected to serve as an effective therapeutic method for atherosclerosis, 4) since lowering plasma cholesterol levels has been proven to reduce mortality from myocardial infarction.5) Acyl-CoA: cholesterol O-acyltransferase (ACAT, EC 2.3.1.26) 6,7) is an intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Previously, we reported that plasma total cholesterol levels in rats fed a high cholesterol diet decreased by 50% when YIC-C8-434 was administered at dose of 2.4 mg/kg/d for 7 d. 8) In the present study, it was clarified that oral administration of YIC-C8-434 directly inhibited both intestinal and hepatic ACAT. It is thus speculated that YIC-C8-434 lowers the total plasma cholesterol level by inhibiting intestinal cholesterol absorption and/or hepatic VLDL cholesterol secretion.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…Previously, we reported that plasma total cholesterol levels in rats fed a high cholesterol diet decreased by 50% when YIC-C8-434 was administered at dose of 2.4 mg/kg/d for 7 d. 8) In the present study, it was clarified that oral administration of YIC-C8-434 directly inhibited both intestinal and hepatic ACAT. It is thus speculated that YIC-C8-434 lowers the total plasma cholesterol level by inhibiting intestinal cholesterol absorption and/or hepatic VLDL cholesterol secretion.…”
Section: Discussionsupporting
confidence: 47%
“…8) In the present study, we investigated the effect of YIC-C8-434 on the formation of cholesteryl esters, triacylglycerols, and phospholipids in Caco2 and HepG2 cell model systems. As shown in Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15) Yakuchinone B and the structural analogues have been extensively studied as inhibitors of acyl-CoA: cholesterol O-acyltransferase that can be therapeutic agents for hypercholesterolemia and atherosclerosis. 16) Yakuchinone B has also been reported to show inhibitory activity of tyrosinase. The a,b-unsaturated carbonyl conjugated moiety and aromatic ring of yakuchinone B play important roles in the competitive inhibition of tyrosinase.…”
mentioning
confidence: 99%